Two pediatric patients with secondary glioblastoma following radiotherapy for acute lymphoblastic leukemia: a case report - Nanae Chiba; Noriyoshi Takahashi; Hiroaki Ogawa; Takaya Yamamoto; Rei Umezawa; Masayuki Kanamori; Hidenori Endo; Keiichi Jingu (World Journal of Surgical Oncology)
Abstract Background Although radiation therapy (RT) has been established as a leading treatment for cancer patients, alongside surgery and chemotherapy, radiation itself is a well-known risk factor for carcinogenesis (Kamran et al., Cancer. 122(12):1809–21, 2016). A second malignant neoplasm may occur even with a small radiation dose (Diallo et al., Int J Radiat Oncol, 74(3):876–83, 2009). Relling et al. estimated that the cumulative risk of the development of malignant brain tumors following prophylactic cranial RT for acute lymphoblastic leukemia (ALL) patients is around 0.5%-1.5% at 15 years (Walter et al., J Clin Oncol Off J Am Soc Clin Oncol, 16(12):3761–7, 1998). The most frequent tumor types of radiation-induced malignant brain tumors are meningioma, glioblastoma (GBM), and sarcoma (Onishi et al., 2024). GBM––the most aggressive type of glioma––is classified as a high-grade glioma as per the WHO classification of tumors (Holland, Proc Natl Acad Sci U S A 97(12):6242–4, 2000; Louis et al., Neuro-Oncol 23(8):1231–51, 2021). GBM still draws attention due to its poor prognosis. The median overall survival (OS) of adult patients with GBM is approximately 12 months, and less than 5% of the patients might survive more than 5 years (Hertler et al., Eur J Cancer 189:112,913, 2023). Whereas the definitive treatment for GBM patients is surgery, adjuvant RT, and chemotherapy, the appropriate re-irradiation dose for patients with radiation-induced GBM (RIGBM) is still controversial since a more critical decision on the radiation dose needs to be made considering that the incidence of brain necrosis increases as the radiation dose increases (Lawrence et al., Int J Radiat Oncol 76(3):S20–7, 2010). Case presentation Two patients at the age of 15 years were found to have RIGBM. The stable health duration until they developed RIGBM was 9–11 years after the first RT for ALL. Total resection was performed in Case 1 and a biopsy was first performed in Case 2 and then total resection was performed. Concurrent chemotherapy and external beam RT (50 Gy in 25 fractions for 5 weeks, 2 Gy in a dose per fraction) were performed in both patients. One patient (Case 1) survived without recurrence for more than 104 months after the initiation of radiation, whereas other patient died due to progression. Conclusion To our knowledge, this is the first case report on long-term survival of a young patient with RIGBM. This case report sheds light on long-term survivors among pediatric RIGBM and the optimal radiation dose in the settings of re-irradiation.